2008
DOI: 10.1111/j.1741-6612.2008.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Personal emergency alarms: What impact do they have on older people's lives?

Abstract: Personal alarms have many positive impacts on the lives of older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 7 publications
1
37
0
3
Order By: Relevance
“…Previous research has also identified that having an alarm can reduce family contact as the family do not feel they have to keep checking on their relative (De San Miguel & Lewin, 2008). Similarly, our study found that 13% of participants with alarms reported that it had had a large impact on reducing contact with family.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Previous research has also identified that having an alarm can reduce family contact as the family do not feel they have to keep checking on their relative (De San Miguel & Lewin, 2008). Similarly, our study found that 13% of participants with alarms reported that it had had a large impact on reducing contact with family.…”
Section: Discussionsupporting
confidence: 59%
“…It has been commonly reported that users of personal alarms experience increased security, peace of mind, and enhanced personal safety from having an alarm (De San Miguel & Lewin, 2008;Johnston, Grimmers-Sommers, & Sutherland, 2010). These previous studies, however, have not involved a comparison group or compared the results of a standardized measure at baseline and follow-up, only collecting reported benefits at a single point in time.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Tele-care was shown to influence improvements in levels of depression, 4 in quality of life, 5 decreasing visits to the emergency room and greater adherence to medical recommendations, 1 support in the case of falls, giving a feeling of security and reduction in anxiety, 2 the perception of more independent life and, with relation to the caregiver/relative, more free time, peace of mind and security. 5 Give the effects that the tele-care program had, the majority recommended the use of these services.…”
Section: Discussionmentioning
confidence: 99%